2001
DOI: 10.2460/ajvr.2001.62.1500
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ingestion of high concentrations of cholecalciferol in cats

Abstract: These results indicate that cats are resistant to cholecalciferol toxicosis when the diet is otherwise complete and balanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…The National Research Council (NRC) 2006 recommendations allow a minimum of 224 IU/kg (5.6 µg/kg) and a maximum of 30,000 IU/kg (750 µg/kg) in the dry matter of cholecalciferol for kittens after weaning. 15 The levels of vitamin D in cats foods should be between the minimum allowance and the safe upper limit, which was established by Sih et al 4 While the dry food (food 2) in this case series contained 978 IU vitamin D 3 /kg (original substance), the wet food that was predominantly given (food 1) had a vitamin D 3 content of 46,900 IU/kg (original substance). Both were measured in a certified laboratory (LUFA-ITL GmbH, Agrolab Laborgruppe, Kiel, Germany).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Research Council (NRC) 2006 recommendations allow a minimum of 224 IU/kg (5.6 µg/kg) and a maximum of 30,000 IU/kg (750 µg/kg) in the dry matter of cholecalciferol for kittens after weaning. 15 The levels of vitamin D in cats foods should be between the minimum allowance and the safe upper limit, which was established by Sih et al 4 While the dry food (food 2) in this case series contained 978 IU vitamin D 3 /kg (original substance), the wet food that was predominantly given (food 1) had a vitamin D 3 content of 46,900 IU/kg (original substance). Both were measured in a certified laboratory (LUFA-ITL GmbH, Agrolab Laborgruppe, Kiel, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory changes in cats with hypervitaminosis D included hypercalcaemia, hyperphosphataemia, alkalosis, high urea and creatinine concentrations, hypercalciuria and a decrease in urine concentrating ability. [1][2][3][4] Case descriptions A 6-month-old sexually intact male British Shorthair cat (cat 1) weighing 2.5 kg presented to the Veterinary Teaching Hospital of the Ludwig Maximilian University of Munich for a 3-week history of polyuria, lethargy and laboured breathing breathing. The cat's littermate (2.3 kg sexuallyintact female -cat 2) also living in their household, showed similar, but less severe, signs.…”
mentioning
confidence: 99%
“…Clinical, laboratory, and histopathologic findings in these cats included vomiting, hypercalcemia, hyperphosphatemia, azotemia, proteinuria, calciuria, phosphaturia, decreased urine specific gravity, and mineralization of various body tissues, particularly the kidneys and walls of large blood vessels [62]. One may speculate as to whether there is indeed a predisposition to impairment of renal function in cats with FORL, because results of experimental studies on cats fed diets high in vitamin D 3 (15,000-33,840 IU/kg of dry matter) were contradictory, ranging from no evidence of detrimental effects on feline health to a high prevalence of renal dysfunction and mortality [65]. Vitamin D and vitamin D metabolites are important regulators of osteoclastic bone resorption [66].…”
Section: Increased Vitamin D Activity In Cats With Feline Odontoclastmentioning
confidence: 99%
“…14 However, when cats were fed a high dietary concentration of 25-OH-D (118 µg/kg versus 846 µg/kg), no adverse effects were observed in terms of renal function during an 18-month period, and renal tissue appeared normal on histological evaluation. 13 Plasma 25-OH-D concentrations increased significantly (1,071.9 ± 115.3 nmol/L) at 18-months. The authors concluded that cats are resistant to cholecalciferol toxicity when the diet is otherwise complete and balanced, although perhaps if the cats were to receive the diet for a longer time, toxic concentrations would eventually develop causing measurable renal damage.…”
Section: Discussionmentioning
confidence: 97%